THIS STUDY CRITICALLY ANALYZES THE THREAT POSED BY THE ABANDONMENT OF SEAFARERS TO VARIOUS ASPECTS OF OCEAN HEALTH - S, Abraham; Prakash G, Aswathy (Journal of Neonatal Surgery, 2025)
The seafarer abandonment continues to be a critical concern in the maritime industry, presenting considerable obstacles to the safeguarding of human rights. This paper examines the underlying issues that contribute to seafarers being abandoned and assesses the current legal frameworks and processes designed to protect their gender equality rights. The research commences by analyzing the fundamental factors that contribute to seafarer abandonment, environmental sustainability of well-being and good health, encompassing economic constraints, insufficient regulations, and the intricacies of international maritime legislation. This statement emphasizes how these variables give rise to loopholes that enable unethical ship-owners to take advantage of and desert seafarers, leaving them without sufficient provisions, salary, or a way to return to their home country. In addition, the report examines the involvement of flag states, port states, and international organizations in addressing the issue of seafarer abandonment. The statement emphasizes the significance of collaboration and coordination among parties to guarantee prompt intervention and assistance for seafarers who have been abandoned. In addition, the analysis takes into account the socio-economic consequences of seafarer abandonment on individuals, families, and communities. It highlights the importance of comprehensive strategies that tackle both current needs and long-term solutions.